The Museum of Modern Love - Rose, Heather, 1964- (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2018)
"Arky Levin has reached a creative dead end. Guilty and restless after an unexpected separation from his wife, almost by chance he stumbles upon an art exhibit that will change his life. Based on a real piece of performance art, the installation that the fictional Arky Levin discovers is inexplicably powerful. Visitors to the Museum of Modern Art sit across a table from artist Marina Abramovi for as short or long a period of time as they choose. Although some go in skeptical, almost all leave moved. And the participants are not the only ones to find themselves changed by this unusual experience: Arky finds himself returning daily to watch others with Abramovi. As the performance unfolds over the course of 75 days, so too does Arky. As he bonds with other people drawn to the exhibit, he slowly starts to understand what might be missing in his life and what he must do"--
"Originally published in Australia in 2016 by Allen & Unwin."
Keywords: Abramovi, Marina -- Exhibitions -- Fiction; Performance art -- Fiction; Film composers -- Fiction; Conduct of life -- Fiction; Man-woman relationships -- Fiction; New York (N.Y.) -- Fiction